Disease-modifying therapies as positive predictors of quality of life for Sudanese patients with multiple sclerosis: a cross-sectional study - Omar, Eman Saleh; Suliman, Hayat M; Osman, Bashier; Abdalla, Safa A; Abdoon, Iman Hassan (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2024)
BackgroundMultiple sclerosis (MS) is an immune-mediated, neurodegenerative disease with devastating, disabling, and negative impacts on the patients’ quality of life (QoL). Although MS was not known in Sudan, it seems to be rising in recent years. This is a cross-sectional, hospital-based study aimed at assessing the impact of MS medications on patients’ QoL in neurology clinics in Khartoum City. Sixty-four patients diagnosed with MS were recruited. SF-36 questionnaire was used to assess the patients’ QoL. Data were collected from patients’ records in addition to the hand-delivered questionnaire. Data were analyzed using ANOVA test and logistic regression; p ≤ 0.05 was considered statistically significant.ResultsThe majority of patients were females from north Sudan (92.2%). The mean age was 28.2 ± 6.5. Relapsing–remitting was the most diagnosed MS type (65.6%). Fatigue and urinary incontinence were the most observed symptoms. All patients had vitamin D deficiency (5–20 ng/ml). Disease-modifying therapies (DMTs) were prescribed to 37.5% of patients.The overall mean QoL was 53.9 ± 14.7 with fair physical and mental health (51.8 ± 19.2 and 57.0 ± 10.9, respectively). Patients on DMTs showed a significantly good QoL compared to azathioprine (p ≤ 0.01), corticosteroids (p ≤ 0.01.), and no medications (p ≤ 001). Azathioprine (OR = 0.12; p ≤ 0.05), corticosteroids (OR = 0.14; p ≤ 0.05) and no treatment (OR = 0.01; p ≤ 0.001) negatively affected MS patients’ QoL when compared to DMTs. Vitamin D supplementation was significantly (p ≤ 0.01) associated with good QoL.ConclusionsMS was prominent in young females’ descendants of Sudanese northern tribes. DMTs improve the devastating effect of MS on patients’ QoL, and vitamin D supplementation was significantly associated with good QoL of MS patients.